Importance of the swallowing atypical in them malocclusions - Jiménez Jiménez, Jonatan (2016)
This review aims to determine the atypical swallowing malocclusions. When there are inadequate move-ments of the tongue and / or other structures during oral and pharyngolaryngeal phase of swallowing, talking about atypical swallowing, as a non-physiological habit. Its objectives may be multiple, simul-taneously acting alone or cumulatively. The size of a large tongue has been found as an impediment to correct such alternations, though this is a cause of causing malocclusion. the importance of the application of myofunctional therapies for prevention and rehabilitation of soft tissue, as these can cause malocclusions and lack of facial development, affecting the aesthetics of the patient stands.